Choice of implant combinations in total hip replacement: systematic review and network meta-analysis. (2nd November 2017) - López-López, José A; Humphriss, Rachel L; Beswick, Andrew D; Thom, Howard H Z; Hunt, Linda P; Burston, Amanda; Fawsitt, Christopher G; Hollingworth, William; Higgins, Julian P T; Welton, Nicky J; Blom, Ashley W; Marques, Elsa M R
Abstract : Objective  To compare the survival of different implant combinations for primary total hip replacement (THR). Design  Systematic review and network meta-analysis. Data sources  Medline, Embase, The Cochrane Library, ClinicalTrials.gov, WHO International Clinical Trials Registry Platform, and the EU Clinical Trials Register. Review methods  Published randomised controlled trials comparing different implant combinations. Implant combinations were defined by bearing surface materials (metal-on-polyethylene, ceramic-on-polyethylene, ceramic-on-ceramic, or metal-on-metal), head size (large ≥36 mm or small <36 mm), and fixation technique (cemented, uncemented, hybrid, or reverse hybrid). Our reference implant combination was metal-on-polyethylene (not highly cross linked), small head, and cemented. The primary outcome was revision surgery at 0-2 years and 2-10 years after primary THR. The secondary outcome was the Harris hip score reported by clinicians. Results  77 studies were included in the systematic review, and 15 studies (3177 hips) in the network meta-analysis for revision. There was no evidence that the risk of revision surgery was reduced by other implant combinations compared with the reference implant combination. Although estimates are imprecise, metal-on-metal, small head, cemented implants (hazard ratio 4.4, 95% credible interval 1.6 to 16.6) and resurfacing (12.1, 2.1 to 120.3) increase the risk of revision at 0-2 years after primary THR compared with the reference implant combination. Similar results were observed for the 2-10 years period. 31 studies (2888 patients) were included in the analysis of Harris hip score. No implant combination had a better score than the reference implant combination. Conclusions  Newer implant combinations were not found to be better than the reference implant combination (metal-on-polyethylene (not highly cross linked), small head, cemented) in terms of risk of revision surgery or Harris hip score. Metal-on-metal, small head, cemented implants and resurfacing increased the risk of revision surgery compared with the reference implant combination. The results were consistent with observational evidence and were replicated in sensitivity analysis but were limited by poor reporting across studies. Systematic review registration  PROSPERO CRD42015019435.